Middle East respiratory syndrome coronavirus infection in non-camelid domestic mammals. Issue 1 (1st January 2019) - Kandeil, Ahmed; Gomaa, Mokhtar; Shehata, Mahmoud; El-Taweel, Ahmed; Kayed, Ahmed E.; Abiadh, Awatef; Jrijer, Jamel; Moatasim, Yassmin; Kutkat, Omnia; Bagato, Ola; Mahmoud, Sara; Mostafa, Ahmed; et al.
ABSTRACT: Dromedary camels are natural host of the Middle East respiratory syndrome coronavirus (MERS-CoV). However, there are limited studies of MERS-CoV infection of other domestic mammals exposed to infected dromedaries. We expanded our surveillance among camels in Egypt, Tunisia, and Senegal to include other domestic mammalian species in contact with infected camels. A total of 820 sera and 823 nasal swabs from cattle, sheep, goats, donkeys, buffaloes, mules, and horses were collected. Swabs were tested using RT-PCR and virus RNA-positive samples were genetically sequenced and phylogenetically analysed. Sera were screened using virus microneutralization tests and positive sera (where available) were confirmed using plaque reduction neutralization tests (PRNT). We detected 90% PRNT confirmed MERS-CoV antibody in 35 (55.6%) of 63 sera from sheep collected from Senegal, two sheep (1.8%) of 114 in Tunisia and a goat (0.9%) of 107 in Egypt, with titres ranging from 1:80 to ≥1:320. We detected MERS-CoV RNA in swabs from three sheep (1.2%) of 254 and five goats (4.1%) of 121 from Egypt and Senegal, as well as one cow (1.9%) of 53 and three donkeys (7.1%) of 42 from Egypt. Partial sequences of the RT-PCR amplicons confirmed specificity of the results. This study showed that domestic livestock in contact with MERS-CoV infected camels may be at risk of infection. We recommend expanding current MERS-CoV surveillance in animals to include other livestock in close contact with dromedary camels. The segregation of camels from other livestock in farms and live animal markets may need to be considered.